Experimental cyclic tests and retrofit of RC hollow piers - Pedro Delgado (2006)
The main purpose of this paper is to present an experimental campaign of reinforced concrete hollow section piers with different cross sections under cyclic loading, comparing the obtained results with those obtained for the same piers after seismic retrofitting, and evaluating benefits concerning their structural behaviour. The setup of the RC pier experimental tests was designed to carry out cyclic horizontal top displacements with axial load using two orthogonal actuators with a sliding device to allow pier top displacements and rotations, in spite of the vertical actuator being fixed to a steel portal frame. Representative of typical bridge construction, square and rectangular hollow section RC piers were tested at LESE the Laboratory of Earthquake and Structural Engineering at Faculty of Engineering of University of Porto. The structural behaviour and safety improvement of these piers are presented, with the retrofit techniques adopted, as well as the illustration of the external and internal damage pattern. The framework of this study is, therefore, to develop and calibrate procedures enabling the evaluation of the different retrofit solution efficiency, their possibilities and fields of application.